Enzymatic chokepoints and synergistic drug targets in the sterol biosynthesis pathway of Naegleria fowleri. - Wenxu Zhou; Anjan Debnath; Gareth Jennings; Hye Jee Hahn; Boden H Vanderloop; Minu Chaudhuri; W David Nes; Larissa M Podust (PLoS Pathogens, 2018)
Naegleria fowleri is a free-living amoeba that can also act as an opportunistic pathogen causing severe brain infection, primary amebic meningoencephalitis (PAM), in humans. The high mortality rate of PAM (exceeding 97%) is attributed to (i) delayed diagnosis, (ii) lack of safe and effective anti-N. fowleri drugs, and (iii) difficulty of delivering drugs to the brain. Our work addresses identification of new molecular targets that may link anti-Naegleria drug discovery to the existing pharmacopeia of brain-penetrant drugs. Using inhibitors with known mechanism of action as molecular probes, we mapped the sterol biosynthesis pathway of N. fowleri by GC-MS analysis of metabolites. Based on this analysis, we chemically validated two enzymes downstream to CYP51, sterol C24-methyltransferase (SMT, ERG6) and sterol Δ8-Δ7 -isomerase (ERG2), as potential therapeutic drug targets in N. fowleri. The sterol biosynthetic cascade in N. fowleri displayed a mixture of canonical features peculiar to different domains of life: lower eukaryotes, plants and vertebrates. In addition to the cycloartenol→ergosterol biosynthetic route, a route leading to de novo cholesterol biosynthesis emerged. Isotopic labeling of the de novo-synthesized sterols by feeding N. gruberi trophozoites on the U13C-glucose-containing growth medium identified an exogenous origin of cholesterol, while 7-dehydrocholesterol (7DHC) had enriched 13C-content, suggesting a dual origin of this metabolite both from de novo biosynthesis and metabolism of scavenged cholesterol. Sterol homeostasis in Naegleria may be orchestrated over the course of its life-cycle by a "switch" between ergosterol and cholesterol biosynthesis. By demonstrating the growth inhibition and synergistic effects of the sterol biosynthesis inhibitors, we validated new, potentially druggable, molecular targets in N. fowleri. The similarity of the Naegleria sterol Δ8-Δ7 -isomerase to the human non-opioid σ1 receptor, implicated in human CNS conditions such as addiction, amnesia, pain and depression, provides an incentive to assess structurally diverse small-molecule brain-penetrant drugs targeting the human receptor for anti-Naegleria activity.